2004
DOI: 10.1097/01.asn.0000110183.87476.05
|View full text |Cite
|
Sign up to set email alerts
|

Somatic Cell Cloning

Abstract: Abstract. With the increasing difficulties associated with meeting the required needs for organs used in transplantation, alternative approaches need to be considered. These include the use of stem cells as potential sources of specialized cells, the ability to transdifferentiate cell types in culture, and the development of complete organs that can be used in humans. All of the above goals will require a complete understanding of the factors affecting cell differentiation and nuclear reprogramming. To make th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 51 publications
(36 reference statements)
0
12
0
Order By: Relevance
“…In our data set, more than half of cloned pigs were stillborn (23.6%) or died soon after birth (31.4%). Associated pathological changes, such as underweight (average weight of the cloned piglets born under 1000 g: 686.4 +/- 181.0 g; range: 375 – 973 g), which is one of the major causes of early neonatal death, or cleft palate, contracted tendons, or enlarged tongues, have also been observed by other groups [43-47]. We have the impression that the percentage of underweight piglets (among normal weight littermates) is higher in cloned litters.…”
Section: Discussionmentioning
confidence: 74%
“…In our data set, more than half of cloned pigs were stillborn (23.6%) or died soon after birth (31.4%). Associated pathological changes, such as underweight (average weight of the cloned piglets born under 1000 g: 686.4 +/- 181.0 g; range: 375 – 973 g), which is one of the major causes of early neonatal death, or cleft palate, contracted tendons, or enlarged tongues, have also been observed by other groups [43-47]. We have the impression that the percentage of underweight piglets (among normal weight littermates) is higher in cloned litters.…”
Section: Discussionmentioning
confidence: 74%
“…However, compared with other reproductive assistant techniques, scNT cloning is associated with particularly high levels of phenotypic instability (Hill et al, 1999;Cibelli et al, 2002;Hiendleder et al, 2004;Park et al, 2004Park et al, , 2005, as 64% of cattle, 40% of sheep, 60% of pigs, and 93% of mice exhibit some form of abnormality, such as pulmonary hypertension and respiratory distress. For example, goat and pig clones are prone to bacterial infections of the lungs, abnormal numbers of teats, cleft lips, malformed limbs, an atrial septal defect, a cranial abnormality, and contracted tendons Piedrahita et al, 2004;Lee et al, 2005). It should also be noted that many researchers have observed that cloned animals are healthy and normal (Bondioli et al, 2001;Lanza et al, 2001;Lai et al, 2002;Yin et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In our data set, more than half of cloned pigs were stillborn (23.6%) or died soon after birth (31.4%). Associated pathological changes, such as underweight (average weight of the cloned piglets born under 1000 g: 686.4 +/− 181.0 g; range: 375 -973 g), which is one of the major causes of early neonatal death, or cleft palate, contracted tendons, or enlarged tongues, have also been observed by other groups [43][44][45][46][47]. We have the impression that the percentage of underweight piglets (among normal weight littermates) is higher in cloned litters.…”
Section: Figurementioning
confidence: 88%